The use of the Tapering in BPS Mesocycle by AZS AWF Wroclaw athletes - Jan Kosendiak; Jacek Borkowski; Katarzyna Hyjek; Joanna Grobelna; Róża Gumienna (Journal of Education, Health and Sport, 2017)
Athletes, coaches, and sports academics are constantly working to maximize the, so called, sports form during the most important competitions. The form peak is usually achieved by decreasing the training load in the pre-scheduled period before the competition. This period of "cut-down" training is referred to as the tapering (or the taper). Tapering is a complex process affected by the number of factors, including volume, intensity, and frequency of training. If this process is successful, it is possible to achieve the peak form at the time of the major competitions. Tapering can thus become one of the most decisive factors in preparing an athlete for a competition.